One-year evaluation of rotational stability and visual outcomes following horizontal, vertical, and oblique implantation of ICL V4c - Jing Dong; Qi Liu; Bo Qin (BMC Ophthalmology)
Abstract Background To evaluate and compare the rotational stability and visual outcomes of Implantable Collamer Lens (ICL) V4c implantation in horizontal, vertical, and oblique orientations and to identify risk factors contributing to postoperative lens rotation. Methods In this retrospective study, 502 eyes of 265 patients who underwent ICL V4c implantation for myopia correction were analyzed. Patients were categorized into three groups based on implantation orientation: horizontal, vertical, or oblique. Preoperative parameters included uncorrected distance visual acuity (UDVA), corrected distance visual acuity (CDVA), intraocular pressure (IOP), manifest refraction spherical equivalent (MRSE), axial length (AL), anterior chamber depth (ACD), white-to-white (WTW) distance, and sulcus-to-sulcus (STS) measurements. Postoperative evaluations were conducted at 1 year and included UDVA, CDVA, MRSE, IOP, vault measurements, and rotational angles of the ICL. Logistic regression analysis was performed to determine risk factors associated with significant ICL rotation (> 5°). Results All three groups achieved excellent visual outcomes, with 100% of cases attaining postoperative UDVA equal to or better than preoperative CDVA. No statistically significant differences were observed among the groups in terms of postoperative MRSE, IOP, or vault measurements. Although the mean rotational angles were comparable across the groups, the oblique implantation group demonstrated a higher incidence of rotations exceeding 5° compared to the horizontal and vertical groups. Furthermore, larger WTW distances were identified as a significant risk factor for increased rotational instability in the oblique group. Conclusions ICL V4c implantation is a highly effective procedure for myopia correction, providing excellent visual outcomes regardless of implantation orientation. However, oblique implantation, particularly in eyes with larger WTW distances, is associated with a higher risk of postoperative rotational instability. Careful consideration of WTW measurements may help minimize rotational risks in such cases.